The Reduction of Blood Pressure in Elderly People with Hypertension Through Morning Walk Therapy: - - Sia Mawan Yulia Fatmawati; Kusuma Laila Watik; Alvin Abdillah (Universitas STRADA Indonesia, 2024)
Background: Hypertension in the elderly is a very dangerous disease because without early indications it can cause sudden death. The prevalence of people with hypertension in the Burneh Health Center in 2021 is 15.935 people (11.29%). The proportion of elderly with hypertension is 1,820 elderly men (0.10%) and 1,670 elderly women (0.09%). Purpose: This study aims to analyze the effect of morning walking physical activity on reducing systolic blood pressure in elderly people with hypertension. Method: This study was conducted in the village of Burneh, Bangkalan, East Java, Indonesia from May to June 2022. The research design used a Quasy Experiment with a Pre-test and Post-test approach, the independent variable in this study was physical activity therapy for morning walks and the dependent variable systolic blood pressure in elderly with hypertension. The sample size is 14 elderly with purposive sampling technique. Data analysis used the Paired t-test. Results: The results of the statistical test obtained p-value = 0.041 <0.05 indicating that there was a difference in systolic blood pressure before and after being given physical activity therapy for the morning walk. Most of the respondents (57.14%) experienced a decrease in systolic blood pressure with an average decrease of 8.72 mmHg. Conclusion: Therapeutic physical activity walking in the morning has a significant effect on systolic blood pressure in elderly people with hypertension. Health workers need to provide correct information about the benefits of morning walks for elderly people with hypertension and monitor the consistency of sufferers.